Exploited for Sectoral Sustainability: A Systematic Review on the Examination of the Effects of Hazardous Conditions Faced by Migrant Seasonal Farmworkers in Agriculture on Their Health-Related Quality of Life - Theodoros Fouskas; Anastasios Sepetis; Androniki Kavoura (Sustainability, 2026)
While there has been an increase in publications on environmental sustainability in agriculture, the labor aspect of sustainable agriculture remains insufficiently addressed in scientific literature. Migrant seasonal farmworkers (MSFWs) are fundamental to food production, yet often labor under hazardous conditions. This systematic review, conducted in accordance with PRISMA guidelines, synthesizes findings from fourteen peer-reviewed studies across multiple countries that utilized validated health-related quality of life (HRQoL) instruments. This review focuses exclusively on studies employing validated health-related quality of life (HRQoL) instruments, which, while essential for methodological rigor, limited the number of eligible studies. The search was expanded to five major databases to maximize coverage. The review aims to describe the working and living conditions of MSFWs, examine the effects of these hazards on their HRQoL, and explore broader implications for the sustainability of agriculture. The most prevalent detrimental conditions identified include chemical pesticide exposure, underpayment of wages, poor living and working environments, and inadequate labor legislation. Across diverse agricultural contexts, the review confirms the universality of poor working conditions and their consistent negative impacts on farmworker health, wellbeing, and the sustainability of the sector. Addressing the exploitation of migrant farmworkers is essential not only for realizing their rights but also for achieving social, environmental, and economic sustainability in agriculture worldwide. The findings underscore the urgent need for policy reforms to improve labor protections, working conditions, and access to health services for this vulnerable workforce.